Composite diaphragm for electrolysis of water to produce hydrogen and preparation method and device thereof
By using crosslinked polymers formed by modified inorganic nanooxide particles and crosslinked monomers in electrolytic hydrogen production technology, the problem that the polyphenylene sulfide separator cannot effectively isolate the mixing of oxygen and hydrogen is achieved, and a composite separator with good gas isolation, low surface resistance and good mechanical properties is achieved, improving the safety and efficiency of the electrolytic hydrogen production process.
Patent Information
- Application Number
- CN202411076147.9
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2024-08-07
- Publication Date
- 2025-04-11
- Estimated Expiration
- 2044-08-07
AI Technical Summary
In the existing electrolytic hydrogen production technology, the polyphenylene sulfide (PPS) membrane has a large mesh hole diameter and cannot effectively isolate the mixing of oxygen and hydrogen, resulting in poor safety. It is necessary to strictly control the pressure difference between the cathode and anode chambers.
The crosslinked polymer formed by modified inorganic nanooxide particles and crosslinked monomers is modified by silane coupling agent, and crosslinking is carried out in the polymer system to enhance the binding force of the organic and inorganic interface and improve the mechanical and chemical properties of the composite separator.
A composite separator with good air isolation, low surface resistance, high bubble point pressure, good mechanical properties, uniform dispersion of inorganic particles, high chemical stability and good thermal stability is achieved, improving the safety and efficiency of the electrolytic hydrogen production process.
Smart Images

Figure CN118835278B_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of hydrogen production by electrolysis of water, and in particular to a composite diaphragm used for hydrogen production by electrolysis of water and a preparation method and device thereof. Background Art
[0002] In the 21st century, the global demand for clean energy is growing. As a zero-emission hydrogen production technology, water electrolysis has become a global research hotspot. At present, water electrolysis hydrogen production technologies mainly include alkaline water electrolysis, proton exchange membrane (PEM) water electrolysis and solid oxide water electrolysis.
[0003] In the process of producing hydrogen by alkaline water electrolysis, the diaphragm is one of the key components. Its main function is to separate the anode and cathode, while allowing ions to pass through, preventing gas mixing, and maintaining the charge balance inside the electrolyzer. The performance of the diaphragm directly affects the efficiency, stability and safety of the electrolysis process.
[0004] Early electrolysis devices were relatively simple, using natural materials such as asbestos as diaphragms. Asbestos diaphragms have poor mechanical and chemical stability, are toxic in themselves, and are easily degraded in alkaline environments, resulting in short life and low efficiency, and have been eliminated. Currently, the widely used polyphenylene sulfide (PPS) diaphragms have improved the chemical stability and mechanical strength of the diaphragms, but due to the large pore size of the PPS mesh, it cannot effectively isolate the mixing of oxygen and hydrogen, and has poor safety, requiring strict control of the pressure difference between the cathode and anode chambers. Summary of the invention
[0005] Based on this, the present application provides a composite diaphragm with good gas barrier properties for electrolyzing water to produce hydrogen, and a preparation method and device thereof.
[0006] The first aspect of the present application provides a composite diaphragm for producing hydrogen by electrolysis of water, comprising:
[0007] support layer; and
[0008] The composite layer is located on at least one side of the support layer, and the composite layer comprises a polymer and a cross-linked polymer, wherein the cross-linked polymer is formed by polymerizing modified inorganic nano-oxide particles and a cross-linked monomer; the modified inorganic nano-oxide particles are obtained by modifying inorganic nano-oxide particles with a silane coupling agent containing a carbon-carbon double bond, and the cross-linked monomer comprises a photosensitive unsaturated monomer.
[0009] In some embodiments, the crosslinking monomer includes one or more of ethylene glycol diacrylate, trimethylolpropane triacrylate, pentaerythritol tetraacrylate, dipentaerythritol pentaacrylate, and dipentaerythritol hexaacrylate.
[0010] In some embodiments, the modified inorganic nano-oxide particles include one or more of modified silicon dioxide particles, modified titanium dioxide particles, and modified zirconium dioxide particles; and / or
[0011] The average particle size D50 of the modified inorganic nano-oxide particles is 10nm-100nm; and / or
[0012] The silane coupling agent includes one or more of acryloxytriisopropylsilane, 3-(trimethoxysilyl)propyl methacrylate, vinyltriethoxysilane and vinyltrimethoxysilane.
[0013] In some embodiments, the support layer comprises polyphenylene sulfide; and / or
[0014] The polymer includes polysulfone;
[0015] Optionally, the polysulfone material includes one or more of polysulfone, sulfonated polysulfone, polyethersulfone, poly(arylene ether sulfone) and tertiary aminated polysulfone.
[0016] The second aspect of the present application provides a method for preparing a composite diaphragm for producing hydrogen by electrolysis of water according to the first aspect of the present application, comprising the following steps:
[0017] Using a silane coupling agent containing a carbon-carbon double bond to modify the inorganic nano-oxide particles to prepare the modified inorganic nano-oxide particles;
[0018] preparing a casting solution containing the modified inorganic nano-oxide particles, the polymer and a porogen;
[0019] The casting solution is applied to at least one side of the support layer, and pre-evaporation, solidification treatment and light irradiation treatment are performed in sequence to prepare the composite diaphragm; wherein the solidification treatment is performed in a solidification bath containing the cross-linking monomer.
[0020] In some embodiments, the temperature of the modification treatment is 50°C-100°C; and / or the time of the modification treatment is 2h-8h.
[0021] In some embodiments, the wavelength of UV light for the light treatment is 254nm-365nm; and / or the time of the light treatment is 5s-120s.
[0022] In some embodiments, the coagulation bath further comprises water and a photoinitiator;
[0023] Optionally, the photoinitiator includes 2,4,6-trimethylbenzoyldiphenylphosphine;
[0024] Optionally, the mass proportion of the cross-linking monomer in the coagulation bath is 1%-50%;
[0025] Optionally, the mass ratio of the photoinitiator to the cross-linking monomer is 1:(1-3).
[0026] In some embodiments, the preparation method includes at least one of the following conditions:
[0027] (1) The inorganic nano-oxide particles include one or more of silicon dioxide particles, titanium dioxide particles and zirconium dioxide particles;
[0028] (2) The particle size of the inorganic nano-oxide particles is 10nm-200nm;
[0029] (3) The modification treatment comprises: modifying a dispersion liquid containing inorganic nano-oxide particles and a silane coupling agent containing a carbon-carbon double bond;
[0030] Optionally, the solvent of the dispersion includes one or more of N,N dimethylformamide, N,N dimethylacetamide, N-methylpyrrolidone, dimethyl sulfoxide, ethanol and water;
[0031] Optionally, the mass ratio of the inorganic nano-oxide particles to the solvent in the dispersion is 1:(0.8-1.5);
[0032] (4) The mass of the silane coupling agent accounts for 0.1%-10% of the mass of the inorganic nano-oxide particles;
[0033] (5) The mass ratio of the polymer to the inorganic nano-oxide particles is 1:(1-8);
[0034] (6) The porogen includes one or more of polyvinyl pyrrolidone and polyvinyl alcohol;
[0035] (7) The mass of the porogen accounts for 1% to 20% of the mass of the polymer;
[0036] (8) The temperature of the solidification treatment is 0°C-60°C, and the time is 5s-1200s.
[0037] The third aspect of the present application provides a device for producing hydrogen by electrolysis of water, which includes the composite diaphragm for producing hydrogen by electrolysis of water according to the first aspect of the present application or the composite diaphragm for producing hydrogen by electrolysis of water prepared by the preparation method of the second aspect of the present application.
[0038] The composite membrane for producing hydrogen by electrolysis of water provided above, its composite layer comprises a polymer and a cross-linked polymer formed by polymerization of modified inorganic nano-oxide particles and cross-linked monomers, the modified inorganic nano-oxide particles are inorganic nano-oxide particles modified by a silane coupling agent containing a carbon-carbon double bond, and the cross-linked monomers include photosensitive unsaturated monomers; compared with inorganic nano-oxide particles, the modified inorganic nano-oxide particles can be well dispersed in the polymer system, effectively improving the mechanical properties and bubble point pressure of the composite membrane, and reducing the surface resistance; the cross-linked polymerized monomer effectively connects the inorganic nano-oxide particles to the polymer system, enhances the organic-inorganic interface bonding force, and further improves the durability of the composite membrane. Therefore, the present application provides a composite membrane with good gas isolation, low surface resistance, high bubble point pressure, good mechanical properties, uniform dispersion of inorganic particles, high chemical stability, and good thermal stability.
[0039] The preparation method of the composite diaphragm for electrolysis of water to produce hydrogen provided by the present application improves the dispersibility of the inorganic nano-oxide particles in the polymer system by modifying the inorganic nano-oxide particles with a silane coupling agent, effectively improves the mechanical properties and bubble point pressure of the composite diaphragm, and reduces the surface resistance; introduces a silane coupling agent containing a carbon-carbon double bond and a cross-linking monomer into the system, effectively modifies the inorganic nano-oxide particles and connects them to the polymer system, enhances the binding force of the organic-inorganic interface, and further improves the durability of the composite diaphragm. In addition, the modification process adopted in the present application is simple and easy to operate, and the polymerization cross-linking is achieved by UV light, which is easy to industrialize. BRIEF DESCRIPTION OF THE DRAWINGS
[0040] In order to more clearly illustrate the technical solutions in the embodiments of the present application and to more completely understand the present application and its beneficial effects, the following is a brief introduction to the drawings required for the description of the embodiments. Obviously, the drawings described below are only some embodiments of the present application, and those skilled in the art can obtain other drawings based on these drawings without creative work.
[0041] Figure 1 A schematic diagram of a process of solidification and light treatment of a casting solution provided in one embodiment of the present application;
[0042] Figure 2 A schematic diagram of volume particle size distribution of an inorganic nano-oxide particle and an inorganic nano-oxide particle modified with a silane coupling agent containing a carbon-carbon double bond provided in one embodiment of the present application;
[0043] Figure 3 This is a surface scan of the composite membrane in Example 1. DETAILED DESCRIPTION
[0044] For ease of understanding of the present invention, the application will be described more fully below with reference to relevant embodiments. The following provides preferred embodiments of the application. However, the application can be implemented in many different forms and is not limited to the embodiments described herein. On the contrary, the purpose of providing these embodiments is to make the understanding of the disclosure of the application more thorough and comprehensive.
[0045] Unless otherwise defined, all technical and scientific terms used herein have the same meaning as those commonly understood by those skilled in the art to which this application belongs. The terms used herein in the specification of this application are only for the purpose of describing specific embodiments and are not intended to limit this application.
[0046] The terms "and / or", "or / and", and "and / or" used herein include any one of two or more related listed items, and also include any and all combinations of the related listed items, wherein the any and all combinations include any combination of two related listed items, any more related listed items, or all related listed items. It should be noted that when at least three items are connected by at least two conjunctions selected from "and / or", "or / and", and "and / or", it should be understood that in the present application, the technical solution undoubtedly includes technical solutions connected by "logical and", and also undoubtedly includes technical solutions connected by "logical or".
[0047] In the present application, the technical features described in an open manner include closed technical solutions composed of the listed features, and also include open technical solutions containing the listed features.
[0048] In this application, when it comes to numerical ranges, unless otherwise specified, the above numerical ranges are deemed to be continuous and include the minimum and maximum values of the range, as well as each value between such minimum and maximum values. Further, when a range refers to an integer, each integer between the minimum and maximum values of the range is included. In addition, when multiple ranges are provided to describe features or characteristics, the ranges can be merged. In other words, unless otherwise specified, all ranges disclosed herein should be understood to include any and all subranges included therein.
[0049] Only some numerical ranges are specifically disclosed herein. However, any lower limit can be combined with any upper limit to form an unspecified range; and any lower limit can be combined with other lower limits to form an unspecified range, and likewise any upper limit can be combined with any other upper limit to form an unspecified range. In addition, each separately disclosed point or single value can itself be combined as a lower limit or upper limit with any other point or single value or with other lower limits or upper limits to form an unspecified range.
[0050] The temperature parameters in this application, unless otherwise specified, allow both constant temperature treatment and treatment within a certain temperature range. The constant temperature treatment allows the temperature to fluctuate within the accuracy range controlled by the instrument. Fluctuations within the range of ±5°C, ±4°C, ±3°C, ±2°C, and ±1°C are allowed.
[0051] In this application, unless otherwise specified, the size, particle size, and diameter generally refer to the average value. In this application, "particle size" and "particle size" have the same definition, both representing the average particle size of a sphere or a spheroid.
[0052] Herein, the “suitable” mentioned in “suitable combination”, “suitable method”, “any suitable method”, etc., shall be based on the ability to implement the technical solution of this application, solve the technical problems of this application, and achieve the expected technical effects of this application.
[0053] In the present application, "further", "further", "particularly" and the like are used for descriptive purposes to indicate differences in content, but should not be construed as limiting the scope of protection of the present application.
[0054] In this application, "optionally", "optional", and "optional" mean optional or dispensable, that is, any one of the two parallel schemes of "yes" or "no". If multiple "options" appear in a technical solution, unless otherwise specified and there is no contradiction or mutual restriction, each "optional" is independent.
[0055] In the description of the application, "plurality" means at least two, such as two, three, etc., unless otherwise clearly and specifically defined.
[0056] If there is no special description, all embodiments and optional embodiments of the present application can be combined with each other to form a new technical solution. If there is no special description, all technical features and optional technical features of the present application can be combined with each other to form a new technical solution.
[0057] If there is no special explanation, all the steps of the present application can be performed sequentially or randomly, preferably sequentially.
[0058] At present, polyphenylene sulfide (PPS) diaphragms are widely used in the process of alkaline water electrolysis to produce hydrogen, which improves the chemical stability and mechanical strength of the diaphragm. However, due to the large pore size of the PPS mesh, it cannot effectively isolate the mixing of oxygen and hydrogen, and its safety is poor. The pressure difference between the cathode and anode chambers needs to be strictly controlled.
[0059] Based on the above problems, the present application modifies the inorganic nano-oxide particles by a silane coupling agent containing carbon-carbon double bonds to better disperse them in the polymer system, and cross-links them through chemical bonds between the silane coupling agent and the cross-linking monomer to enhance the organic-inorganic interface bonding force and improve the mechanical and chemical properties of the composite diaphragm.
[0060] The first aspect of the present application provides a composite diaphragm for producing hydrogen by electrolysis of water, comprising a support layer and a composite layer located on at least one side of the support layer, the composite layer comprising a polymer and a cross-linked polymer, the cross-linked polymer being formed by polymerization of modified inorganic nano-oxide particles and a cross-linked monomer; the modified inorganic nano-oxide particles are obtained by modifying inorganic nano-oxide particles with a silane coupling agent containing carbon-carbon double bonds, and the cross-linked monomer comprises a water-dispersible polyacrylate.
[0061] When the silane coupling agent used to modify the inorganic nano-oxide particles contains a carbon-carbon double bond, it is conducive to a cross-linking reaction with a cross-linking monomer.
[0062] When photosensitive unsaturated monomers are selected as cross-linking monomers, since the photosensitive unsaturated monomers can be dispersed in non-solvent water, during the preparation of the composite diaphragm, the photosensitive unsaturated monomers can be better introduced into the diaphragm matrix through the coagulation bath step, and cross-linking is initiated by UV light, the process is simple, and the operability is strong.
[0063] Understandably, the composite membrane for producing hydrogen by electrolysis of water provided above, its composite layer comprises a polymer and a cross-linked polymer formed by polymerization of modified inorganic nano-oxide particles and cross-linked monomers, the modified inorganic nano-oxide particles are inorganic nano-oxide particles modified by a silane coupling agent containing a carbon-carbon double bond, and the cross-linked monomers include photosensitive unsaturated monomers; compared with inorganic nano-oxide particles, the modified inorganic nano-oxide particles can be well dispersed in the polymer system, effectively improving the mechanical properties and bubble point pressure of the composite membrane, and reducing the surface resistance; the cross-linked polymerized monomer effectively connects the inorganic nano-oxide particles to the polymer system, enhances the organic-inorganic interface bonding force, and further improves the durability of the composite membrane. Therefore, the present application provides a composite membrane with good gas isolation, low surface resistance, high bubble point pressure, good mechanical properties, uniform dispersion of inorganic particles, high chemical stability, and good thermal stability.
[0064] In some embodiments, the crosslinking monomer includes one or more of ethylene glycol diacrylate, trimethylolpropane triacrylate, pentaerythritol tetraacrylate, dipentaerythritol pentaacrylate and dipentaerythritol hexaacrylate. Thus, it is soluble in water, highly reactive, and can be induced to undergo a crosslinking reaction using UV light.
[0065] As a possible implementation, the modified inorganic nano-oxide particles include one or more of modified silicon dioxide particles, modified titanium dioxide particles, and modified zirconium dioxide particles. That is, the modified inorganic nano-oxide particles include one or more of silicon dioxide particles, titanium dioxide particles, and zirconium dioxide particles modified with a silane coupling agent containing a carbon-carbon double bond.
[0066] In some exemplary embodiments, the average particle size D50 of the modified inorganic nano-oxide particles is 10nm-100nm; for example, it can be but not limited to 10nm, 20nm, 30nm, 40nm, 50nm, 60nm, 70nm, 80nm, 90nm, 100nm or the range between any two of the above particle sizes, etc. When the particle size of the modified inorganic nano-oxide particles is within the above range, it is beneficial to improve the mechanical strength of the prepared composite diaphragm, and at the same time, it can improve hydrophilicity, reduce surface resistance, and reduce energy consumption.
[0067] In some embodiments, the silane coupling agent includes one or more of acryloxytriisopropylsilane, 3-(trimethoxysilyl)propyl methacrylate, vinyltriethoxysilane, and vinyltrimethoxysilane.
[0068] In some embodiments, the support layer comprises polyphenylene sulfide.
[0069] In some alternative embodiments, the polymer comprises a polysulfone.
[0070] As a possible implementation, the polysulfone material includes one or more of polysulfone, sulfonated polysulfone, polyethersulfone, poly(arylene ether sulfone) and tertiary aminated polysulfone.
[0071] The second aspect of the present application provides a method for preparing a composite diaphragm for producing hydrogen by electrolysis of water according to the first aspect of the present application, comprising the following steps:
[0072] Inorganic nano-oxide particles are modified by using a silane coupling agent containing a carbon-carbon double bond to prepare modified inorganic nano-oxide particles; a casting solution containing modified inorganic nano-oxide particles, a polymer and a porogen is prepared; the casting solution is applied to at least one side of a support layer, and pre-evaporation, solidification treatment and light treatment are performed in sequence to prepare a composite diaphragm; wherein the solidification treatment is performed in a solidification bath containing a cross-linking monomer.
[0073] Understandably, the preparation method of the composite diaphragm for electrolysis of water to produce hydrogen provided by the present application improves the dispersibility of the inorganic nano-oxide particles in the polymer system by modifying the inorganic nano-oxide particles with a silane coupling agent, effectively improves the mechanical properties and bubble point pressure of the composite diaphragm, and reduces the surface resistance; introduces a silane coupling agent containing a carbon-carbon double bond and a cross-linking monomer into the system, effectively modifies the inorganic nano-oxide particles and connects them to the polymer system, enhances the binding force of the organic-inorganic interface, and further improves the durability of the composite diaphragm. In addition, the modification process adopted in the present application is simple and easy to operate, and the polymerization cross-linking is achieved by UV light, which is easy to industrialize.
[0074] Figure 1 A schematic diagram of a process of solidification and light treatment of a casting solution provided in an embodiment; Figure 1 As shown, the modified inorganic nano-oxide particles have good dispersibility in the polymer system. After coagulation and light treatment, the modified inorganic nano-oxide particles polymerize with the cross-linking monomer to form a polymer, which effectively modifies the inorganic nano-oxide particles and connects them to the polymer system, thereby enhancing the bonding strength of the organic-inorganic interface.
[0075] In some embodiments, the temperature of the modification treatment is 50°C-100°C; for example, it can be but not limited to 50°C, 55°C, 60°C, 65°C, 70°C, 75°C, 80°C, 85°C, 90°C, 95°C, 100°C or a range between any two of the above temperatures, etc. When the temperature of the modification treatment is within the above range, it is conducive to the modification treatment.
[0076] As a possible implementation, the modification treatment time is 2h-8h; for example, it can be but not limited to 2h, 2.5h, 3h, 3.5h, 4h, 4.5h, 5h, 5.5h, 6h, 6.5h, 7h, 7.5h, 8h or a range between any two of the above times, etc. When the modification treatment time is within the above range, it is conducive to complete modification treatment reaction.
[0077] It should be noted that the temperature and time of the modification treatment can be combined in any appropriate manner, and both can be selected from any temperature and time of the modification treatment described in this article.
[0078] As a possible implementation, the wavelength of UV light for light treatment is 254nm-365nm. When the wavelength of UV light for light treatment is within the above range, the energy required for the reaction can be achieved, thus promoting the occurrence of the cross-linking reaction.
[0079] In some optional embodiments, the light treatment time is 5s-120s; for example, it can be but not limited to 5s, 10s, 15s, 20s, 25s, 30s, 35s, 40s, 45s, 50s, 55s, 60s, 65s, 70s, 75s, 80s, 85s, 90s, 95s, 100s, 105s, 110s, 115s, 120s or a range between any two of the above times, etc. When the light treatment time is within the above range, it is conducive to the completion of the cross-linking reaction and reduces energy consumption.
[0080] It should be noted that the UV light wavelength and time of the light irradiation treatment can be combined in any appropriate manner, and both can be selected from any UV light wavelength and time of the light irradiation treatment described in this document.
[0081] In some embodiments, the coagulation bath further comprises water and a photoinitiator.
[0082] In some alternative embodiments, the photoinitiator includes 2,4,6-trimethylbenzoyldiphenylphosphine.
[0083] As a possible implementation, the mass proportion of the cross-linking monomer in the coagulation bath is 1%-10%; for example, it can be but not limited to 1%, 1.5%, 2%, 2.5%, 3%, 3.5%, 4%, 4.5%, 5%, 5.5%, 6%, 6.5%, 7%, 7.5%, 8%, 8.5%, 9%, 9.5%, 10% or the range between any two of the above mass proportions. When the mass proportion of the cross-linking monomer in the coagulation bath is within the above range, it is beneficial to improve the mechanical properties of the prepared composite diaphragm, especially to improve the tensile strength.
[0084] In some exemplary embodiments, the mass ratio of the photoinitiator to the crosslinking monomer is 1:(1-3); for example, it can be, but is not limited to, 1:1, 1:1.1, 1:1.2, 1:1.3, 1:1.4, 1:1.5, 1:1.6, 1:1.7, 1:1.8, 1:1.9, 1:2, 1:2.1, 1:2.2, 1:2.3, 1:2.4, 1:2.5, 1:2.6, 1:2.7, 1:2.8, 1:2.9, 1:3 or a range between any two of the above ratios. When the mass ratio of the photoinitiator to the crosslinking monomer is within the above range, it is beneficial to initiate the polymerization of the crosslinking monomer and to improve the mechanical strength of the prepared composite diaphragm.
[0085] In some embodiments, the inorganic nano-oxide particles include one or more of silica particles, titania particles, and zirconium dioxide particles.
[0086] As a possible implementation, the particle size of the inorganic nano-oxide particles is 10nm-800nm; for example, it can be but not limited to 10nm, 20nm, 30nm, 40nm, 50nm, 60nm, 70nm, 80nm, 90nm, 100nm, 110nm, 120nm, 130nm, 140nm, 150nm, 160nm, 170nm, 180nm, 190nm, 200nm or the range between any two of the above particle sizes, etc. When the particle size of the inorganic nano-oxide particles is within the above range, it is beneficial to improve the effect of the modification treatment, and at the same time, it is beneficial to improve the mechanical properties and electrochemical properties of the prepared composite diaphragm.
[0087] Figure 2 The volume particle size distribution diagram of the inorganic nano-oxide particles and the modified inorganic nano-oxide particles provided in one embodiment is as follows: Figure 2 It can be seen that after modification, the particle size distribution of nano-ions is more uniform and the particle size is smaller.
[0088] In some embodiments, the modification process includes: performing a modification process on a dispersion liquid containing inorganic nano-oxide particles and a silane coupling agent containing a carbon-carbon double bond.
[0089] As a possible implementation, the solvent of the dispersion includes one or more of N,N-dimethylformamide, N,N-dimethylacetamide, N-methylpyrrolidone, dimethyl sulfoxide, ethanol and water.
[0090] As a possible implementation, the mass ratio of inorganic nano-oxide particles to solvent in the dispersion is 1:(0.8-1.5); for example, it can be but not limited to 1:0.8, 1:0.9, 1:1, 1:1.1, 1:1.2, 1:1.3, 1:1.4, 1:1.5 or a range between any two of the above ratios. When the mass ratio of inorganic nano-oxide particles to solvent is within the above range, it is conducive to achieving efficient dispersion of inorganic nano-oxide particles and improving the mechanical properties and electrochemical properties of the composite membrane prepared by the composite.
[0091] In some embodiments, the method for preparing the dispersion includes: dispersing inorganic nano-oxide particles in a solvent, mechanically stirring at a speed of 500rpm-2500rpm to fully disperse the inorganic nano-oxide particles in the solvent; and then adding a silane coupling agent containing a carbon-carbon double bond to prepare the dispersion.
[0092] In some optional embodiments, the mass of the silane coupling agent containing carbon-carbon double bonds accounts for 0.1%-10% of the mass of the inorganic nano-oxide particles; for example, it can be but not limited to 0.1%, 0.5%, 1%, 1.5%, 2%, 2.5%, 3%, 3.5%, 4%, 4.5%, 5%, 5.5%, 6%, 6.5%, 7%, 7.5%, 8%, 8.5%, 9%, 9.5%, 10% or the range between any two of the above values. When the mass percentage of the silane coupling agent to the mass of the inorganic nano-oxide particles is within the above range, it is beneficial to modify the inorganic nano-oxide particles.
[0093] In some embodiments, the mass ratio of the polymer to the inorganic nano-oxide particles is 1:(1-10); for example, it can be, but is not limited to, 1:1, 1:1.5, 1:2, 1:2.5, 1:3, 1:3.5, 1:4, 1:4.5, 1:5, 1:5.5, 1:6, 1:6.5, 1:7, 1:7.5, 1:8, 1:9, 1:10 or a range between any two of the above ratios. When the mass ratio of the polymer to the inorganic nano-oxide particles is within the above range, the prepared composite diaphragm has better surface resistance, bubble point, mechanical properties and tensile strength.
[0094] In some exemplary embodiments, the porogen includes one or more of polyvinyl pyrrolidone and polyvinyl alcohol.
[0095] As a possible implementation, the mass of the porogen accounts for 1%-20% of the mass of the polymer; for example, it can be but not limited to 1%, 2%, 3%, 4%, 5%, 6%, 7%, 8%, 9%, 10%, 11%, 12%, 13%, 14%, 15%, 16%, 17%, 18%, 19%, 20% or the range between any two of the above values. When the mass of the porogen accounts for the mass of the polymer within the above range, it is beneficial for the prepared composite membrane to have a better surface resistance.
[0096] In some embodiments, the temperature of the coagulation treatment is 0°C-60°C; for example, it can be but is not limited to 0°C, 5°C, 10°C, 15°C, 20°C, 25°C, 30°C, 35°C, 40°C, 45°C, 50°C, 55°C, 60°C or a range between any two of the above temperatures.
[0097] In some embodiments, the coagulation treatment time is 5s-1200s; for example, it may be but not limited to 5s, 50s, 100s, 200s, 300s, 400s, 500s, 600s, 700s, 800s, 900s, 1000s, 1100s, 1200s or a range between any two of the above times.
[0098] In some embodiments, the amount of coagulation bath used is sufficient to immerse the membrane.
[0099] In some embodiments, the method for preparing the casting solution includes: adding a polymer to the modified dispersion, stirring at a speed of 500rpm-3000rpm for 4h-24h, adding a porogen, and after the porogen is evenly dispersed, performing a degassing treatment to prepare the casting solution.
[0100] The third aspect of the present application provides a device for producing hydrogen by electrolysis of water, including the composite diaphragm for producing hydrogen by electrolysis of water according to the first aspect of the present application or the composite diaphragm for producing hydrogen by electrolysis of water prepared by the preparation method of the second aspect of the present application.
[0101] The technical scheme of the present invention is described in detail below in conjunction with specific embodiments. It should be understood that these embodiments are only used to illustrate the present invention and are not intended to limit the scope of the present invention. The experimental methods for which specific conditions are not specified in the following embodiments are preferably referred to the guidance given in the present invention, and can also be carried out according to the experimental manual or conventional conditions in the art, or according to the conditions recommended by the manufacturer, or with reference to experimental methods known in the art.
[0102] In the following specific embodiments, the measured parameters of raw material components may have slight deviations within the range of weighing accuracy unless otherwise specified. For temperature and time parameters, acceptable deviations caused by instrument test accuracy or operation accuracy are allowed.
[0103] 1. Preparation of composite diaphragm
[0104] Example 1
[0105] Step S1: Disperse 150g of nano-titanium dioxide particles (as inorganic nano-oxide particles) in 120mL of N,N-dimethylformamide solvent, disperse at a speed of 2000r / min for 5h, add 1g of vinyltriethoxysilane (as a silane coupling agent containing carbon-carbon double bonds), raise the temperature to 60°C, react for 6h, wait for the solution to cool, add 30g of polysulfone (as a polymer), fully dissolve at room temperature at a speed of 2000r / min for 24h, add 1g of polyvinylpyrrolidone (as a porogen) and stir for 1h to obtain a uniformly dispersed casting solution.
[0106] Step S2: Coat the casting solution onto the supporting material polyphenylene sulfide (PPS) mesh cloth, and place it in the air for pre-evaporation. Immerse it in a coagulation bath at room temperature for phase inversion, wherein the coagulation bath consists of 80wt% water, 10wt% dipentaerythritol pentaacrylate (as a cross-linking monomer) and 10wt% 2,4,6-trimethylbenzoyldiphenylphosphine (as a photoinitiator). After the diaphragm is completely cured, place it under 356nm UV light for cross-linking reaction for 30s to obtain a cross-linked composite diaphragm.
[0107] Figure 3 is a surface scan of the composite diaphragm obtained in Example 1. Figure 3 It can be seen that the nano-ions on the surface of the composite membrane are evenly distributed.
[0108] Example 2
[0109] Step S1: Disperse 120g of nano-titanium dioxide particles (as inorganic nano-oxide particles) in 120mL of N,N-dimethylformamide solvent, disperse at 2000r / min for 5h, add 5g of vinyltriethoxysilane (as a silane coupling agent containing carbon-carbon double bonds), raise the temperature to 60°C, react for 3h, wait for the solution to cool, add 30g of polysulfone (as a polymer), fully dissolve at room temperature at 2000r / min for 12h, add 1g of polyvinylpyrrolidone (as a porogen) and stir for 1h to obtain a uniformly dispersed casting solution.
[0110] Step S2: Coat the casting solution onto the supporting material polyphenylene sulfide (PPS) mesh cloth and place it in the air for pre-evaporation. Immerse it in a coagulation bath at room temperature for phase inversion, wherein the coagulation bath consists of 80wt% water, 10wt% dipentaerythritol pentaacrylate (as a cross-linking monomer) and 10wt% 2,4,6-trimethylbenzoyldiphenylphosphine (as a photoinitiator). After the diaphragm is completely cured, place it under 356nm UV light for 60s of cross-linking reaction to obtain a cross-linked composite diaphragm.
[0111] Example 3
[0112] Step S1: Disperse 150g of nano-titanium dioxide particles (as inorganic nano-oxide particles) in 120mL of N-methylpyrrolidone solvent, disperse at 2500r / min for 3h, add 1g of 3-(trimethoxysilyl)propyl methacrylate (as a silane coupling agent containing carbon-carbon double bonds), heat to 80°C, react for 3h, wait for the solution to cool, add 25g of polysulfone (as a polymer), fully dissolve at 2000r / min at room temperature for 8h, add 0.6g of polyvinylpyrrolidone (as a porogen) and stir for 1h to obtain a uniformly dispersed casting solution.
[0113] Step S2: Coat the casting solution onto the supporting material polyphenylene sulfide (PPS) mesh cloth and place it in the air for pre-evaporation. Immerse it in a coagulation bath at room temperature for phase inversion, wherein the coagulation bath consists of 70wt% water, 20wt% dipentaerythritol pentaacrylate (as a cross-linking monomer) and 10wt% 2,4,6-trimethylbenzoyldiphenylphosphine (as a photoinitiator). After the membrane is completely cured, place it under 254nm UV light for cross-linking reaction for 60s to obtain a cross-linked composite membrane.
[0114] Example 4
[0115] Step S1: Disperse 150g of nano zirconium dioxide particles (as inorganic nano oxide particles) in 120mL of N-methylpyrrolidone solvent, disperse at 2500r / min for 3h, add 1g of 3-(trimethoxymethylsilyl)propyl methacrylate (as a silane coupling agent containing carbon-carbon double bonds), heat to 80°C, react for 3h, wait for the solution to cool, add 25g of polysulfone (as a polymer), fully dissolve at 2000r / min at room temperature for 24h, add 0.6g of polyvinylpyrrolidone (as a porogen) and stir for 1h to obtain a uniformly dispersed casting solution.
[0116] Step S2: Coat the casting solution onto the supporting material polyphenylene sulfide (PPS) mesh cloth and place it in the air for pre-evaporation. Immerse it in a coagulation bath at room temperature for phase inversion, wherein the coagulation bath consists of 70wt% water, 20wt% dipentaerythritol pentaacrylate (as a cross-linking monomer) and 10wt% 2,4,6-trimethylbenzoyldiphenylphosphine (as a photoinitiator). After the membrane is completely cured, place it under 254nm UV light for cross-linking reaction for 60s to obtain a cross-linked composite membrane.
[0117] Example 5
[0118] Step S1: Disperse 120g of nano zirconium dioxide particles (as inorganic nano oxide particles) in 120mL of N-methylpyrrolidone solvent, disperse at 2500r / min for 3h, add 5g of 3-(trimethoxysilyl)propyl methacrylate (as a silane coupling agent containing carbon-carbon double bonds), heat to 80°C, react for 3h, wait for the solution to cool, add 28g of polysulfone (as a polymer), fully dissolve at 2000r / min at room temperature for 12h, add 0.6g of polyvinylpyrrolidone (as a porogen) and stir for 1h to obtain a uniformly dispersed casting solution.
[0119] Step S2: Coat the casting solution onto the supporting material polyphenylene sulfide (PPS) mesh cloth and place it in the air for pre-evaporation. Immerse it in a coagulation bath at room temperature for phase inversion, wherein the coagulation bath consists of 70wt% water, 20wt% dipentaerythritol pentaacrylate (as a cross-linking monomer) and 10wt% 2,4,6-trimethylbenzoyldiphenylphosphine (as a photoinitiator). After the membrane is completely cured, place it under 254nm UV light for cross-linking reaction for 60s to obtain a cross-linked composite membrane.
[0120] Example 6
[0121] Step S1: Disperse 80g of nano zirconium dioxide particles (as inorganic nano oxide particles) in 120mL of N-methylpyrrolidone solvent, disperse at 2000r / min for 3h, add 5g of 3-(trimethoxysilyl)propyl methacrylate (as a silane coupling agent containing carbon-carbon double bonds), heat to 80°C, react for 3h, wait for the solution to cool, add 30g of polysulfone (as a polymer), fully dissolve at 2000r / min at room temperature for 8h, add 1.2g of polyvinylpyrrolidone (as a porogen) and stir for 1h to obtain a uniformly dispersed casting solution.
[0122] Step S2: Coat the casting solution onto the supporting material polyphenylene sulfide (PPS) mesh cloth and place it in the air for pre-evaporation. Immerse it in a coagulation bath at room temperature for phase inversion, wherein the coagulation bath consists of 70wt% water, 20wt% dipentaerythritol pentaacrylate (as a cross-linking monomer) and 10wt% 2,4,6-trimethylbenzoyldiphenylphosphine (as a photoinitiator). After the membrane is completely cured, place it under 254nm UV light for cross-linking reaction for 60s to obtain a cross-linked composite membrane.
[0123] Example 7
[0124] Step S1: Disperse 100g of nano-titanium dioxide particles (as inorganic nano-oxide particles) in 120mL of N,N-dimethylacetamide solvent, disperse at 2000r / min for 5h, add 2g of acryloxytriisopropylsilane (as a silane coupling agent containing carbon-carbon double bonds), raise the temperature to 100°C, react for 3h, wait for the solution to cool, add 28g of polysulfone (as a polymer), fully dissolve at room temperature at 2500r / min for 10h, add 0.5g of polyvinyl alcohol ketone (as a porogen) and stir for 1h to obtain a uniformly dispersed casting solution.
[0125] Step S2: Coat the casting solution onto the supporting material polyphenylene sulfide (PPS) mesh cloth and place it in the air for pre-evaporation. Immerse it in a coagulation bath at room temperature for phase inversion, wherein the coagulation bath consists of 80wt% water, 10wt% dipentaerythritol pentaacrylate (as a cross-linking monomer) and 10wt% 2,4,6-trimethylbenzoyldiphenylphosphine (as a photoinitiator). After the diaphragm is completely cured, place it under 356nm UV light for 60s of cross-linking reaction to obtain a cross-linked composite diaphragm.
[0126] Example 8
[0127] Step S1: Disperse 130 g of nano zirconium dioxide particles (as inorganic nano oxide particles) in 130 mL of N,N-dimethylformamide solvent, disperse at 2000 r / min for 5 h, add 5 g of vinyltrimethoxysilane (as a silane coupling agent containing carbon-carbon double bonds), raise the temperature to 60°C, react for 3 h, wait for the solution to cool, add 26 g of polysulfone (as a polymer), fully dissolve at 2000 r / min at room temperature for 4 h, add 2.5 g of polyvinyl pyrrolidone (as a porogen) and stir for 1 h to obtain a uniformly dispersed casting solution.
[0128] Step S2: The casting solution is coated on the supporting material polyphenylene sulfide (PPS) mesh cloth, and placed in the air for pre-evaporation. It is immersed in a coagulation bath at room temperature for phase inversion, wherein the coagulation bath consists of 80wt% water, 10wt% dipentaerythritol pentaacrylate (as a cross-linking monomer) and 10wt% 2,4,6-trimethylbenzoyldiphenylphosphine. After the diaphragm is completely cured, it is placed under 356nm UV light for cross-linking reaction for 60s to obtain a cross-linked composite diaphragm.
[0129] Example 9
[0130] Step S1: Disperse 80g of nano-titanium dioxide particles (as inorganic nano-oxide particles) in 120mL of N,N-dimethylacetamide solvent, disperse at 2500r / min for 2h, add 2g of acryloxytriisopropylsilane (as a silane coupling agent containing carbon-carbon double bonds), raise the temperature to 100°C, react for 3h, wait for the solution to cool, add 28g of polysulfone (as a polymer), fully dissolve at room temperature at 2500r / min for 8h, add 0.5g of polyvinyl alcohol ketone (as a porogen) and stir for 1h to obtain a uniformly dispersed casting solution.
[0131] Step S2: Coat the casting solution onto the supporting material polyphenylene sulfide (PPS) mesh cloth, and place it in the air for pre-evaporation. Immerse it in a coagulation bath at room temperature for phase inversion, wherein the coagulation bath consists of 80wt% water, 10wt% dipentaerythritol pentaacrylate (as a cross-linking monomer) and 10wt% 2,4,6-trimethylbenzoyldiphenylphosphine (as a photoinitiator). After the diaphragm is completely cured, place it under 356nm UV light for cross-linking reaction for 30s to obtain a cross-linked composite diaphragm.
[0132] Example 10
[0133] Step S1: Disperse 100g of nano-silica particles (as inorganic nano-oxide particles) in 120mL of N,N-dimethylacetamide solvent, disperse at 2000r / min for 5h, add 2g of acryloxytriisopropylsilane (as a silane coupling agent containing carbon-carbon double bonds), raise the temperature to 100°C, react for 6h, wait for the solution to cool, add 28g of polysulfone (as a polymer), fully dissolve at room temperature at 2500r / min for 12h, add 0.5g of polyvinyl alcohol ketone (as a porogen) and stir for 1h to obtain a uniformly dispersed casting solution.
[0134] Step S2: Coat the casting solution onto the supporting material polyphenylene sulfide (PPS) mesh cloth and place it in the air for pre-evaporation. Immerse it in a coagulation bath at room temperature for phase inversion, wherein the coagulation bath consists of 80wt% water, 10wt% dipentaerythritol pentaacrylate (as a cross-linking monomer) and 10wt% 2,4,6-trimethylbenzoyldiphenylphosphine (as a photoinitiator). After the diaphragm is completely cured, place it under 356nm UV light for 60s of cross-linking reaction to obtain a cross-linked composite diaphragm.
[0135] Comparative Example 1
[0136] Step S1: 150g of nano titanium dioxide particles (as inorganic nano oxide particles) are dispersed in 120mL of N,N-dimethylformamide solvent, dispersed at a speed of 2000r / min for 5h, 1g of γ-glycidyloxypropyltrimethoxysilane (KH560, a silane coupling agent without carbon-carbon double bonds) is added, the temperature is raised to 60°C, and the reaction is performed for 8h. After the solution is cooled, 20g of polysulfone (as a polymer) is added, and the mixture is fully dissolved at a speed of 2000r / min at room temperature for 4h. 0.5g of polyvinyl pyrrolidone (as a porogen) is added and stirred for 1h to obtain a uniformly dispersed casting solution.
[0137] Step S2: Coat the casting solution onto the supporting material polyphenylene sulfide (PPS) mesh cloth, and place it in the air for pre-evaporation. Immerse it in water at room temperature for phase inversion, and take it out after the membrane is completely solidified to obtain an organic-inorganic composite membrane.
[0138] Comparative Example 2
[0139] The step S1 in Comparative Example 2 is the same as that in Example 1, except that the step S2 is different. The specific steps of step S2 are as follows:
[0140] Step S2: After the casting solution is prepared, the casting solution is coated on the supporting material polyphenylene sulfide (PPS) mesh cloth, and left to stand in the air for pre-evaporation. It is immersed in water at room temperature for phase inversion, and taken out after the membrane is completely solidified to obtain an organic-inorganic composite membrane.
[0141] Comparative Example 3
[0142] Comparative Example 3 is the same as step S1 in Example 1, except that the cross-linking monomer used in the coagulation bath in step S2 is different; the details are as follows:
[0143] Step S2: Coat the casting solution onto the supporting material polyphenylene sulfide (PPS) mesh cloth and place it in the air for pre-evaporation. Immerse it in a coagulation bath at room temperature for phase inversion, wherein the coagulation bath consists of 80wt% water, 10wt% cyclohexene (as a cross-linking monomer) and 10wt% 2,4,6-trimethylbenzoyldiphenylphosphine (as a photoinitiator). After the membrane is completely cured, place it under 356nm UV light for cross-linking reaction for 30s to obtain a cross-linked composite membrane.
[0144] Comparative Example 4
[0145] The difference between Comparative Example 4 and Example 1 is that no vinyl triethoxysilane is added when preparing the casting solution in step S1; and step S2 is the same. Step S1 is specifically as follows:
[0146] Step S1: Disperse 150 g of nano-titanium dioxide particles (as inorganic nano-oxide particles) in 120 mL of N,N-dimethylformamide solvent at a speed of 2000 r / min for 5 hours, then add 30 g of polysulfone (as a polymer) and fully dissolve it at a speed of 2000 r / min at room temperature for 24 hours, add 1 g of polyvinyl pyrrolidone (as a pore-forming agent) and stir for 1 hour to obtain a uniformly dispersed casting solution.
[0147] Comparative Example 5
[0148] The difference between Comparative Example 5 and Example 1 is that: in step S1, γ-glycidyloxypropyltrimethoxysilane (KH560, a silane coupling agent without carbon-carbon double bonds) is used instead of vinyltriethoxysilane; step S2 is the same. Step S1 is specifically as follows:
[0149] Step S1: 150 g of nano titanium dioxide particles (as inorganic nano oxide particles) are dispersed in 120 mL of N,N-dimethylformamide solvent, dispersed at a speed of 2000 r / min for 5 h, 1 g of γ-glycidyloxypropyltrimethoxysilane (KH560, a silane coupling agent without carbon-carbon double bonds) is added, the temperature is raised to 60°C, and the reaction is performed for 6 h. After the solution is cooled, 30 g of polysulfone (as a polymer) is added, and the mixture is fully dissolved at a speed of 2000 r / min at room temperature for 24 h. 1 g of polyvinyl pyrrolidone (as a porogen) is added and stirred for 1 h to obtain a uniformly dispersed casting solution.
[0150] The composite diaphragms prepared in the above Examples 1-10 and Comparative Examples 1-5 were tested for bubble point pressure, surface resistance, porosity and tensile strength, and the test methods were as follows:
[0151] Bubble point pressure: Place the separation membrane sample used for testing in the test liquid for 2 hours to make it completely soaked.
[0152] Place the fully wetted wet membrane sample in the membrane holder; tighten the locking ring of the membrane holder, inject the test liquid into the liquid reservoir, and keep the liquid level 2mm~3mm higher than the membrane surface. A small amount of gas can be introduced through the regulating valve to keep the liquid level unchanged; slowly increase the gas pressure and record the pressure when the first series of continuous bubbles appears in the center of the liquid reservoir.
[0153] Surface resistance: a) Cut the sample to be tested into 5 pieces slightly larger than the size of the test plywood;
[0154] b) Soak the sample in a potassium hydroxide solution at a temperature of (25±2)°C for 4 h;
[0155] c) Adjust the upper electrode plate so that it contacts the lower electrode plate, apply 1kg pressure to the upper electrode plate, connect the upper and lower electrode plates to the positive and negative test clips of the AC low resistance meter, and read the resistance value R1 when the phase is 0;
[0156] d) Place the test diaphragm between the upper and lower electrode plates and measure the resistance value R2 of the sample;
[0157] 3) Test results
[0158] Substitute the test results into the calculation formula (8) to calculate its area resistance. Take the arithmetic mean of the 5 samples as the test result
[0159] R surface = (R2-R1) × S (8)
[0160] Where:
[0161] R is the area resistance of the diaphragm, Ω·cm 2 ;
[0162] R1 is the device body resistance, Ω;
[0163] R2 is the resistance of the device body and diaphragm, Ω;
[0164] S is the effective area of the electrode, cm2.
[0165] Porosity: in accordance with the provisions of GB / T 21650.1-2008.
[0166] Tensile strength: According to the provisions of GB / T 1040.3-2006, a type 2 specimen with a size of (150±0.5)×(15±0.1) mm is selected, the initial distance of the fixture is (100±5) mm, and the test rate is 100 mm / min. The tensile strength is calculated according to the provisions of GB / T1040.3-2006
[0167] The test results of the above items are shown in Table 1.
[0168] Table 1
[0169]
[0170] From the comparison of the results of Examples 1-10 and Comparative Examples 1-5 in the table, it can be seen that compared with Comparative Examples 1-5, the composite diaphragm of Examples 1-10 has higher bubble point pressure, porosity and tensile strength as a whole, and has lower surface resistance, indicating that the present application provides a composite diaphragm with good gas isolation, low surface resistance, high bubble point pressure and good mechanical properties.
[0171] From the comparison of the results of Example 1 and Comparative Examples 2-5, it can be seen that when preparing the composite membrane, the introduction of a silane coupling agent containing a carbon-carbon double bond and a water-dispersible polyacrylate into the system has a synergistic effect. The use of a silane coupling agent to modify the inorganic nano-oxide particles improves the dispersibility of the inorganic nano-oxide particles in the polymer system, effectively improves the mechanical properties and bubble point pressure of the composite membrane, and reduces the surface resistance; the introduction of a silane coupling agent containing a carbon-carbon double bond and a cross-linking monomer into the system effectively modifies the inorganic nano-oxide particles and connects them to the polymer system, enhances the bonding force of the organic-inorganic interface, and further improves the durability of the composite membrane.
[0172] The technical features of the above-described embodiments may be arbitrarily combined. To make the description concise, not all possible combinations of the technical features in the above-described embodiments are described. However, as long as there is no contradiction in the combination of these technical features, they should be considered to be within the scope of this specification.
[0173] The above-mentioned embodiments only express several implementation methods of the present invention, and the descriptions thereof are relatively specific and detailed, but they cannot be understood as limiting the scope of the invention patent. It should be pointed out that, for ordinary technicians in this field, several variations and improvements can be made without departing from the concept of the present invention, and these all belong to the protection scope of the present invention. Therefore, the protection scope of the patent of the present invention shall be subject to the attached claims.
Claims
1. A composite diaphragm for producing hydrogen by electrolysis of water, characterized in that: include: a support layer, the support layer comprising polyphenylene sulfide; and The composite layer is located on at least one side of the support layer, and the composite layer comprises a polymer and a cross-linked polymer, wherein the cross-linked polymer is formed by polymerizing modified inorganic nano-oxide particles and a cross-linked monomer; the modified inorganic nano-oxide particles are obtained by modifying inorganic nano-oxide particles with a silane coupling agent containing a carbon-carbon double bond, and the cross-linked monomer comprises a photosensitive unsaturated monomer; and the polymer comprises a polysulfone substance.
2. The composite diaphragm for producing hydrogen by electrolysis of water according to claim 1, characterized in that: The cross-linking monomer includes one or more of ethylene glycol diacrylate, trimethylolpropane triacrylate, pentaerythritol tetraacrylate, dipentaerythritol pentaacrylate and dipentaerythritol hexaacrylate.
3. The composite diaphragm for producing hydrogen by electrolysis of water according to claim 1, characterized in that: The modified inorganic nano-oxide particles include one or more of modified silicon dioxide particles, modified titanium dioxide particles and modified zirconium dioxide particles; and / or The average particle size D50 of the modified inorganic nano-oxide particles is 10nm-100nm; and / or The silane coupling agent includes one or more of acryloxytriisopropylsilane, 3-(trimethoxysilyl)propyl methacrylate, vinyltriethoxysilane and vinyltrimethoxysilane.
4. The composite diaphragm for producing hydrogen by electrolysis of water according to any one of claims 1 to 3, characterized in that: The polysulfone material includes one or more of polysulfone, sulfonated polysulfone, polyethersulfone, poly(arylene ether sulfone) and tertiary aminated polysulfone.
5. A method for preparing a composite diaphragm for producing hydrogen by electrolysis of water according to any one of claims 1 to 4, characterized in that: The steps include: Using a silane coupling agent containing a carbon-carbon double bond to modify the inorganic nano-oxide particles to prepare the modified inorganic nano-oxide particles; preparing a casting solution containing the modified inorganic nano-oxide particles, the polymer and a porogen; The casting solution is applied to at least one side of the support layer, and pre-evaporation, solidification treatment and light irradiation treatment are performed in sequence to prepare the composite diaphragm; wherein the solidification treatment is performed in a solidification bath containing the cross-linking monomer.
6. The preparation method according to claim 5, characterized in that: The temperature of the modification treatment is 50°C-100°C; and / or the time of the modification treatment is 2h-8h.
7. The preparation method according to claim 5, characterized in that: The wavelength of UV light for the light treatment is 254nm-365nm; and / or the time of the light treatment is 5s-120s.
8. The preparation method according to claim 5, characterized in that: The coagulation bath also contains water and a photoinitiator.
9. The preparation method according to claim 8, characterized in that: The photoinitiator includes 2,4,6-trimethylbenzoyldiphenylphosphine.
10. The preparation method according to claim 8, characterized in that: The cross-linking monomer accounts for 1% to 50% by mass in the coagulation bath.
11. The preparation method according to claim 8, characterized in that: The mass ratio of the photoinitiator to the cross-linking monomer is 1:(1-3).
12. The preparation method according to any one of claims 5 to 11, characterized in that: The preparation method comprises at least one of the following conditions: (1) The inorganic nano-oxide particles include one or more of silicon dioxide particles, titanium dioxide particles and zirconium dioxide particles; (2) The particle size of the inorganic nano-oxide particles is 10nm-200nm; (3) The modification treatment comprises: modifying a dispersion liquid containing inorganic nano-oxide particles and a silane coupling agent containing a carbon-carbon double bond; (4) The mass of the silane coupling agent accounts for 0.1%-10% of the mass of the inorganic nano-oxide particles; (5) The mass ratio of the polymer to the inorganic nano-oxide particles is 1:(1-10); (6) The porogen includes one or more of polyvinyl pyrrolidone and polyvinyl alcohol; (7) The mass of the porogen accounts for 1% to 20% of the mass of the polymer; (8) The temperature of the solidification treatment is 0°C-60°C, and the time is 5s-1200s.
13. The preparation method according to claim 12, characterized in that: The solvent of the dispersion liquid includes one or more of N,N dimethylformamide, N,N dimethylacetamide, N-methylpyrrolidone, dimethyl sulfoxide, ethanol and water.
14. The preparation method according to claim 12, characterized in that: The mass ratio of the inorganic nano-oxide particles to the solvent in the dispersion is 1:(0.8-1.5).
15. A device for producing hydrogen by electrolyzing water, characterized in that: It comprises the composite diaphragm for producing hydrogen by electrolysis of water as claimed in any one of claims 1 to 4 or the composite diaphragm for producing hydrogen by electrolysis of water prepared by the preparation method as claimed in any one of claims 5 to 14.
Citation Information
Patent Citations
Gel composite polymer electrolyte membrane, preparation method thereof and lithium ion battery
CN109755644A